The Utilization of Coconut Water Waste As a Growth Media of the In-Vitro Potato Cutting - Hafsan Hafsan; Muhammad Khalifah Mustami; Masriany Masriany; Isna Rasdianah Aziz; Mustakim Mustakim (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
The limited number of potato seed caused the demand The demand to be unfulfilled especially in South Sulawesi. The use of pathogen-free seeds is absolutely necessary that can be obtained through tissue culture. This study aims to determine the effect of adding coconut water on the growth of in vitro potato plant cuttings and the most effective type of treatment. This research used Varying Concentration of the coconut water, then measure its effect on potato growth (a high number of leaves and plantlets). This study consisted of 4 treatments: TQ0 (without coconut milk), TQ1 (100 ml/l), TQ2 (150ml/l), and TQ3 (200 ml/l). The results showed that the addition of coconut water on the growth of micro cuttings of potato (Solanum tuberosum L.) gave significant effect on the observed parameters, leaf number and plantlets weight. While TQ2 gave the best effect on the growth of in vitro micro cutting of potato.